Panel Data Analysis: Population Size and Development Inequality in Relation to Poverty in East Kalimantan Province - Lisa Puspitasari; Abdul Hakim (Journal of Economics and Business UBS, 2026)
Poverty remains a critical socioeconomic challenge in East Kalimantan Province despite its abundant natural resources. This study aimed to analyze the effects of population size and regional development inequality on poverty levels across 10 districts/cities in East Kalimantan during the 2022–2025 period. A quantitative approach using panel data regression analysis was employed, utilizing secondary data obtained from the Central Statistics Agency (BPS). The sample consisted of 40 observations selected through saturated sampling. The analysis was conducted using EViews 13 software, with the Common Effect Model (CEM) selected as the most appropriate model based on the Chow, Hausman, and Lagrange Multiplier tests. The results indicated that both population size and development inequality had positive and significant effects on poverty levels, both partially and simultaneously. The regression coefficient for population size (0.004198, p = 0.0006) indicated that a 1% increase in population size was associated with a 0.41% increase in poverty levels, while the development inequality coefficient (43.37810, p = 0.0003) demonstrated a stronger influence on poverty. The adjusted R² value of 50.1% indicated that the two variables explained approximately half of the variation in poverty levels. These findings support Malthusian theory and Kuznets’ hypothesis while aligning with recent studies on the development paradox in East Kalimantan. Poverty alleviation strategies should prioritize equitable development policies and improvements in human resource quality, particularly in disadvantaged areas, to achieve sustainable poverty reduction in East Kalimantan.